Pharmacokinetics of teicoplanin in an ICU population of children and infants - Lukas, JC; Karikas, G; Gazouli, M.; Kalabalikis, P; Hatzis,T.; Macheras, P. (PHARMACEUTICAL RESEARCH, 2004)
{Purpose. Better dosing is needed for antibiotics, including teicoplanin (TEI), to prevent emergence of resistant bacterial strains. Here, we assess the TEI pharmacokinetics (PK) related to a 10 mg/l minimum inhibitory concentration (MIC) target in ICU children (4 to 120 months; n=20) with gram+infections. Methods. Standard administration of TEI was with three 10 mg/kg Q12h, loading infusions, and maintainance with 10 mg/kg or 15 mg/kg Q24h. During maintenance, 9 samples (3/day) were collected per patient and the PK analyzed with Nonlinear Mixed Effects Model (NONMEM). Results. Thirty-five percent of concentrations in older children (greater than or equal to2 months) vs. 8% in younger infants (<12 months) were below the target MIC. The global bicompartmental population PK parameters were {[}mean (interindividual CV%)] CL=0.23 l/h {[}72%]
Keywords: Children; infants; NONMEM; Pharmacokinetics; simulation; Teicoplanin